2018
DOI: 10.1155/2018/9897581
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Ameliorates Angiotensin II-Induced Myocardial Fibrosis by Upregulating Peroxisome Proliferator-Activated Receptor Gamma in Young Male Rats

Abstract: Angiotensin (Ang) II contributes to the formation and development of myocardial fibrosis. Ghrelin, a gut peptide, has demonstrated beneficial effects against cardiovascular disease. In the present study, we explored the effect and related mechanism of Ghrelin on myocardial fibrosis in Ang II-infused rats. Adult Sprague-Dawley (SD) rats were divided into 6 groups: Control, Ang II (200ng/kg/min, microinfusion), Ang II+Ghrelin (100 μg/kg, subcutaneously twice daily), Ang II+Ghrelin+GW9662 (a specific PPAR-γ inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 41 publications
(44 reference statements)
1
15
0
Order By: Relevance
“…In the same study, no differences in GHSR density were observed in the RA or the LV between the ischemic heart disease or dilated cardiomyopathy to the control tissues 30 . Our findings also showed no changes in myocardial GHSR as measured by Cy5-ghrelin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), and a relatively weak correlation with ghrelin, suggesting that more dramatic changes in GHSR may occur at the site of vascular tissue injury or dysfunction.…”
Section: Discussionsupporting
confidence: 39%
See 3 more Smart Citations
“…In the same study, no differences in GHSR density were observed in the RA or the LV between the ischemic heart disease or dilated cardiomyopathy to the control tissues 30 . Our findings also showed no changes in myocardial GHSR as measured by Cy5-ghrelin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), and a relatively weak correlation with ghrelin, suggesting that more dramatic changes in GHSR may occur at the site of vascular tissue injury or dysfunction.…”
Section: Discussionsupporting
confidence: 39%
“…Biopsy samples from the left ventricle (LV) and right atrium (RA) were obtained from 25 patients with valvular disease (of whom 13 also had coronary artery disease) and preserved left ventricular ejection fraction, and compared to control samples that were obtained via autopsy. Using quantitative confocal fluorescence microscopy, levels of GHSR were determined using a fluorescent peptide analog of ghrelin, Cy5-ghrelin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19); ghrelin, the heart failure marker natriuretic peptide type-b (BNP), and contractility marker sarcoplasmic reticulum ATPase pump (SERCA2a) were measured by immunofluorescence. A positive correlation between GHSR and ghrelin was apparent in diseased tissue, but not in control tissue.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, angiotensin is widely used to construct myocardial fibrosis model, but the dosage and time point have not reached a unified standard. Research showed that myocardial fibrosis could be induced by continuous infusion of angiotensin at different rates of 0.2 or 2.0 μg/kg/min (no mice died during the 4 weeks of Ang II infusion) [121], 200 ng/kg/min [122], 1.5 μg/day [123] and 0.83 μg/kg/min [124], 400 ng/kg/min [125], and 0.7 mg/kg/d [126] via an osmotic minipump for 4 weeks. In addition, myocardial fibrosis could also be induced by continuous infusion of angiotensin at the rates of 1.5 mg/kg/day [127], 1000 ng/kg/ min [128], 1.1 mg/kg/day [129],and 800 ng/min/kg [130] via an osmotic minipump for 2 weeks.…”
Section: Angiotensin II Angiotensin Ii (Ang Ii) a Central Active Comentioning
confidence: 99%